2011
DOI: 10.1103/physrevlett.107.067402
|View full text |Cite
|
Sign up to set email alerts
|

Spin-PolarizedMn2+Emission from Mn-Doped Colloidal Nanocrystals

Abstract: We report magnetophotoluminescence studies of strongly quantum-confined 0D diluted magnetic semiconductors (DMS), realized in Mn(2+)-doped ZnSe/CdSe core-shell colloidal nanocrystals. In marked contrast to their 3D (bulk), 2D (quantum well), 1D (quantum wire), and 0D (self-assembled quantum dot) DMS counterparts, the ubiquitous yellow emission band from internal d-d ((4)T(1)→(6)A(1)) transitions of the Mn(2+) ions in these nanocrystals is not suppressed in applied magnetic fields and does become circularly pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 35 publications
4
46
2
1
Order By: Relevance
“…[1][2][3][4] Compared to their bulk counterparts, [5][6][7][8][9] magnetically doped semiconductor QDs could provide control of the magnetic ordering, [10][11][12][13][14][15][16] with the onset of magnetization at substantially higher temperatures. [17][18][19][20][21] Experiments typically focus on Mn-doped II-VI and III-V QDs, in which it is possible to include both single [22][23][24][25] and several magnetic impurities, [17][18][19][20][21][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] having similarities with nuclear spins. 41,42 In the first case (single magnetic ion), such systems could be considered as potential quantum bits, quantum memories, or probes to detect an unconventional orbital ordering.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Compared to their bulk counterparts, [5][6][7][8][9] magnetically doped semiconductor QDs could provide control of the magnetic ordering, [10][11][12][13][14][15][16] with the onset of magnetization at substantially higher temperatures. [17][18][19][20][21] Experiments typically focus on Mn-doped II-VI and III-V QDs, in which it is possible to include both single [22][23][24][25] and several magnetic impurities, [17][18][19][20][21][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] having similarities with nuclear spins. 41,42 In the first case (single magnetic ion), such systems could be considered as potential quantum bits, quantum memories, or probes to detect an unconventional orbital ordering.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Mn emission which is basically a spin and orbital forbidden emission does not demonstrate any polarization 58 as expected and is shown in Figure 6 a and b. Surprisingly, it was observed that in three dimensionally confined QDs, Mn emission was observed to be polarized in the presence of magnetic field 59 as shown in Figure 6 c and d. Though, a complete understanding of the polarization of Mn emission is not yet achieved, it can be expected that due to confinement, we observe stronger overlap of wave functions leading to unexpected results.…”
Section: Properties Of Dms Qdsmentioning
confidence: 77%
“…Typically, they are easily synthesized II-VI materials, such as ZnTe, ZnSe, CdS, and CdSe, 91,92 which offer a large size-induced tunability of the transition energies and long spin decoherence times. 93,94 Magnetic doping 95 of these colloidal dots provides an opportunity for a versatile control of magnetic order as well as leads to robust magnetic polaron formation with effective internal magnetic field approaching 100 T. 43,[95][96][97][98][99] …”
Section: Discussionmentioning
confidence: 99%